Proposição de modelo de cobrança pelos serviços de coleta e disposição final de resíduos sólidos domiciliares para o município de Rio Claro - SP - Chagas, Mariana de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Article 19 of the National Solid Waste Policy (PNRS) provides for charging the collection and disposal of household waste, but few municipalities in the country have a charging system for these services. One of the factors that hinder the formulation of a charging system in the municipalities of Brazil is the lack of consensus about the calculation basis that should be used, therefore this research aims to elaborate a scenario of financial sustainability for collection and final disposal services of household waste in Rio Claro - SP, by charging for the collection and disposal of household waste based on water consumption. For the relationship between waste generation and water consumption, two collection routes were selected according to the socioeconomic standard, one represented middle class neighborhoods and the other lower middle class neighborhoods. The months chosen in this research were June and December, considering the variation of waste generation for different periods of the year. The Autonomous Department of Water and Wastewater (DAAE) of Rio Claro provided the water consumption data in each category (residential, commercial) for the selected routes. Thus, it was possible to make monthly waste cost ratios per establishment and per m³ of water consumed. The results obtained demonstrated that charging values for solid waste collection and disposal services ranged from R$ 6,84 to R$ 12,96 per month per residence for the year 2018 and from R$ 10,98 a R$ 20,70 per month per residence for the year 2022, both considering a residence of 3 people. The proposed charging model based on water consumption could enable the financial sustainability of the system.

No Artigo 19 da Política Nacional de Resíduos Sólidos (PNRS) é previsto a cobrança pelos serviços de coleta e disposição final de resíduos sólidos, porém poucos municípios do país apresentam um sistema de cobrança por esses serviços. Um dos fatores que dificulta a realização de um sistema de cobrança nos municípios do Brasil é a falta de consenso a respeito da base de cálculo que deve ser utilizada, dessa forma a presente pesquisa tem como objetivo elaborar um cenário de sustentabilidade financeira para os serviços de coleta e destinação final dos resíduos domiciliares de Rio Claro - SP, por meio da cobrança pelos serviços de coleta e disposição final dos resíduos domiciliares com base no consumo de água. Para a relação entre a geração de resíduos e o consumo de água foram selecionadas duas rotas de coleta de acordo com o padrão socioeconômico, uma representava bairros de classe média e a outra bairros de classe média baixa. Os meses escolhidos para essa pesquisa foram junho e dezembro tendo em vista a variação de geração de resíduos para diferentes períodos do ano. O Departamento Autônomo de Água e Esgoto (DAAE) de Rio Claro forneceu os dados de consumo de água em cada categoria (residencial, comercial) presente nas rotas selecionadas. Assim, foi possível fazer relações de custo mensal de resíduo por estabelecimento e por m³ de agua consumida. Os resultados obtidos demonstraram que os valores de cobrança pelos serviços de coleta e disposição final de resíduos sólidos variaram de R$ 6,84 a R$ 12,96 por mês por residência para o ano de 2018 e de R$ 10,98 a R$ 20,70 por mês por residência para o ano de 2022, ambos considerando uma residência de 3 pessoas. O modelo de cobrança proposto baseado no consumo de água viabilizaria a sustentabilidade financeira do sistema.
Proposition of a charging model for collection and final disposal services of household solid waste in municipality Rio Claro - SP
Keywords: Household solid waste; Charging environmental services; Solid waste tax; Water consumption; Financial sustainability; Resíduos sólidos domiciliares; Cobrança serviços ambientais; Taxa de resíduos sólidos; Consumo de água; Sustentabilidade financeira